Sewage Management - Kılıç Taşeli, Başak (Sustainable Development, 2023)
Sewage management refers to the process of collecting, treating, and disposing of the millions of gallons of wastewater produced daily by households, industries, and commercial establishments. It is vital to treat and dispose of this wastewater appropriately to safeguard public health and the environment. The objective of sewage management is to decrease the number of pollutants in wastewater before it is discharged into water bodies or reused for other purposes. Sewage management is a crucial element of modern society, yet it is frequently disregarded or taken for granted. This book offers a comprehensive overview of the various aspects of sewage management, covering the basics of wastewater treatment and disposal, and the various technologies and processes involved in sewage treatment. Additionally, the book provides case studies of successful sewage management practices from around the world, highlighting best practices and innovative solutions. It is hoped that this e-book will serve as a valuable resource for anyone seeking to better understand this critical aspect of modern society.